Quality management of cultural heritage : problems and best practices : proceedings of the XVII UISPP World Congress (1-7 September 2014, Burgos, Spain), - Quagliuolo, Maurizio,; Delfino, Davide, 1976- (Archaeopress archaeology., 2016)
This work covers Session A13 of the proceedings of XVII UISPP World Congress held between 1-7 September 2017 in Burgos, Spain.